PENGEMBANGAN E-MODUL PADA MATERI TEOREMA PYTHAGORAS BERBASIS PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) BERBANTUAN FLIP PDF PROFESSIONAL - Rajak, Nur Andraini; Ismail, Sumarno; Usman, Kartin (JURNAL MathEdu (Mathematic Education Journal), 2025)
This research aims to develop an e-module on the topic of the Pythagorean Theorem using the RealisticMathematics Education (RME) approach, assisted by Flip PDF Professional The background of thisresearch was the low level of students mathematical understanding, the limited availability of teachingmaterials, and the suboptimal use of technology in the learning process at SMP Negeri 2 Randangan. Theresearch followed the five stages of the ADDIE development model, namely. Analysis, Design,Development, Implementation, and Evaluation. The results of the expert validation for media and contentshowed that the developed e-module fell into the "valid" category, with average scores of 3.36 and 3.37,respectively. The practicality tests also yielded excellent results, with a practicality percentage of 92.50%from teachers and 89.49% from students, both categorized as "very practical." Therefore, this e-modulewas considered suitable and effective for use as a learning resource, particularly for teaching thePythagorean Theorem. It was also found to enhance student engagement and understanding through acontextual and interactive approach.